Chronic leptospirosis in pigs cases of sow abortion in industrial pig farms - ΧΟΝΤΟΥ, ΑΛ.; ΚΥΡΙΑΚΗΣ, ΣΠ.; ΣΙΜΟΣ, ΕΥΑΓ.; ΣΤΟΦΟΡΟΣ, ΕΥΘ.; ΞΥΛΟΥΡΗ, Ε.; ΠΑΝΝΑΚΟΠΟΥΛΟΥ, Λ. (Journal of the Hellenic Veterinary Medical Society, 2019)
After a review about the existing data in relation with leptospirosis in pigs from the international and local literature, the authors described in detail 7 recent cases of chronic leptospirosis in modern industrial pig farms of S. Greece, during the last 15 months with a high level of abortion in the sows, as the main symptom. This is the first reported case of leptospirosis in pigs, from modern indutrial farms, since all previous cases were diagnosed in primitive farms during 1950's and 1960's. The main causes of leptospirosis were: L. pomona, L. tarassovi and L. grip potyphosa. Because of the economical implications of leptospirosis in pig production and also because this disease is dangerous for the human, the authors proposed special programme for the control, prevention, treatment and eradication of the disease in Greece.